Study on Properties of Tapioca Resin Polymer - Jamiluddin, Jaafar; J. P., Siregar; A., Sulaiman; K. A. A., Jalal; Tezara, C. (Universiti Malaysia Pahang, 2016)
Environmental, global warming, renewability, recyclability, and biodegradability issues have encourage scientists and engineers to partially substitute petrochemical-based polymers with green polymers such as natural fiber polymer composites. The major drawback in the development of natural fiber polymer composites is in the incompatibility between matrix and fiber processing temperature of the high temperature of the matrix based on petroleum and low degradation temperature for natural fiber. Creation of PLA as a green matrix provides alternative and solution for incompatibility issue between natural fiber and petroleum based matrix. In this work, the physical, thermal and mechanical properties of PLA from tapioca were reported by reviewing the compatibility between natural fiber and PLA tapioca resin polymer. Density test, hardness test, thermo gravimetric analysis, differential scanning calorimetric and tensile test with different injection temperature sample has been conducted in order to study the compatibility capability. As a conclusion the optimum processing temperature for PLA tapioca resin biopolymer was finalized for development of natural fiber reinforced tapioca resin biopolymer composite.